Ḍilā’ al-Kharāfati ‘alā al-Tarbiyyati fī al-‘Asr al-‘Abbasī - Hasan Basri (Journal of Arabic Literature (JaLi), 2020)
Although the establishment of Abbasid Dynasty was based on bloodshed, the dynasty had experienced golden periods, and one of them was education. That phenomenon was marked by the rise of Baitul Hikmah library which was the meeting point of sciences either from the west (Greece) or the east (India, Persia, and China). Then, Muslim experts developed them into various sciences, such as mathematics, philosophy, astronomy, medicine, physics, metaphysics, and literature. This article aimed to describe forms of fable in Abbasid dynasty, and the impact of fable in education during Abbasid dynasty. This study employed descriptive qualitative method by literature review approach based on post-positivism philosophy. In collecting the data, the study uses various techniques, such as reading and writing. To test the validity of the data, the author applied triangulation method. The data were analyzed through data reduction, data display, and conclusion. The results of this research showed that the fable forms in Abbasid dynasty are fable translation, while the impact of fable to education in Abbasid dynasty is moral learning effort of Abbasid dynasty’s society.